Monitoring Monitoring Lokasi Komponen Alat Berat Berbasis Internet Of Things Pada PT. Thiess BSF Batakan - Mayda Waruni Kasrani; Aswadul Fitri Saiful Rahman; Rizky Ramadoni (Lembaga Penelitian Universitas Balikpapan, 2023)
Abstract— In the digital era like today, every company is competing to innovate to reduce operational costs and increase productivity, one of which is PT. Thiess. Indirectly this also has an impact on the performance of every employee in the company to speed up and maximize work processes with minimal human resources without reducing aspects of occupational safety and health from both government regulations and company standards. As one of the employees who also acts as a researcher at PT. Thiess Balikpapan Support Facility (BSF), the researchers will discuss the problems in finding heavy equipment components. Based on the context of the difficulties described above, researchers will examine the use of Global Position System (GPS) technology. The process of making this prototype uses the NodeMCU ESP8266 microcontroller and GPSMV2 which also functions as a connection to the internet. The results of searching for GPS coordinates are made in the form of localhost using XAMPP, can be viewed in web form and forwarded to Google Maps.